An Assessment of Groundwater Quality of Ashaka and Environs, Gombe, North Eastern Nigeria, Using Water Quality Index Technique - I.A Kwami; A. I. Haruna; A. S. Maigari; A. Lawal; S. Mukkafa; A. Yusuf; M. B, Usman; U. Abubakar; A. G. Mohammed; A. D. Umar; S. U. Umar; I. I. Kariya; et al. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study assesses the quality of the groundwater in Ashaka and environs using the Water Quality Index (WQI) with a view of determining the suitability of the water for public use.. WQI is a technique that uses numbers to portray the quality of water of a given area within a given time based on the level of concentration of selected water quality parameters. This research considered fifteen (15) parameters, including pH, TH, EC, TDS, Mg+2, Ca+2, K+, Na+, SO4-2, Fe2+, HCO3-, Cl-, NO3-, PO4-, and F-, for the computation of the WQI. Fifty water samples were utilized for the WQI and the values were in the range of 34.78 to 820.76, with an average of 122.40. Fourteen percent (7 samples) of the samples exhibited excellent water quality, Thirty-six percent (18 samples) were classified as good quality water, Forty-four percent (22 samples) were categorized as poor quality water, Four percent (2 samples) were identified as very poor quality water, and Two percent (1 sample) were deemed unfit for consumption. the good water quality are found around northern part where as the poor quality water are mostly concentrated at the southern portion of the study area. The poor WQI observed in the area can be a result of high levels of TDS, and elevated concentrations of Magnesium, Sodium, Potassium, Chloride, Sulphate, Nitrate, and TH, exceeding the WHO recommended values for drinking water. The presence of these ions in high concentrations could be a result of applications of fertilizer for agricultural activities and limestone blasting for industrial activities.